Aktualizacja wyceny rzeczowych aktywów trwałych do wartości godziwej w warunkach polskich – związek z kapitalizacją rynkową oraz przyszłą rentownością spółek - Piosik, Andrzej (Revaluation of fixed tangible assets in Poland – association with market performance and future profitability of companies, 2008)
The objective of the paper is to test whether revaluations of tangible fixed assets have been associated with market capitalization of companies listed on the Warsaw Stock Exchange. The next purpose is to check whether revaluations have been correlated with the future operating profits of companies. The analyses are based on the data for 37 companies listed on the Warsaw stock Exchange that performed revaluations between 2004 and 2006. The paper supports the conclusion that book values including revaluation of tangible fixed assets explain the variation in P/BV ratios (price to book value) of companies listed on the Warsaw Stock Exchange. With the help of the regression model estimated on the basis of data for the years 2004- 2005 we have demonstrated that the variability of P/BV ratios in 2005 can be explained by changes in operating profits (or net profits) and changes in revaluation reserves. The variables have been scaled by book value of total assets before revaluations. The estimated model has explained 67% of P/BV ratios variability. We have rejected null hypotheses that the estimated parameters are equal to zero using t statistics. The similar model was estimated for the years 2004-2006 and it has helped explain the variation in P/BV ratios for 2006. We have also demonstrated that revaluations of tangible fixed assets are significantly positively correlated with future operating profits of companies. We have tested that future operating profits (the sum of profits in 2006 and 2007) depend on three variables: operating profits in 2004 and 2005, revaluation reserve and increase in net working capital (between 2004 and 2006). The model explains ca. 70% of total variability of operating profits. The estimates are statistically significant. The inde-pendent and dependent variables were scaled with market value of stock at the end of 2006.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 15, s. 368-380